Local Wisdom-Based Community Adaptation to Ground Movement Phenomenon: A Community Resilience Perspective - Triwicaksono, Wijayanto Dhewa Sary; Kurniawan, Edi (Jurnal Sains Sosio Humaniora, 2026)
This study aims to analyze landslide phenomena, identify forms of local wisdom, and examine community adaptation strategies in coping with ground movement. The novelty of this study lies in the development of an integrated understanding of how local wisdom operates as a community adaptation system by linking empirical environmental knowledge, social values, and collective practices with anticipatory, responsive, and transformative adaptation strategies. A qualitative descriptive case study approach was employed involving 15 participants, including affected residents, village officials, and community leaders selected through the triangulation technique. Data were collected through field observations, semi-structured interviews, and documentation. Data validity was ensured through source, technique, and time triangulation, while data were analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing and verification. The findings reveal that landslide events have occurred progressively since 2019, primarily triggered by prolonged heavy rainfall, causing damage to settlements, public facilities, and infrastructure, while increasing community vulnerability. Local wisdom is reflected in empirical environmental knowledge, mutual cooperation, reforestation practices, drainage maintenance, and compliance with village regulations. These elements collectively support anticipatory, responsive, and transformative adaptation strategies that enhance community resilience to landslide hazards. This study extends the disaster risk reduction literature by demonstrating that local wisdom is not merely a cultural asset but an integrated community-based adaptation system that can serve as a practical reference for strengthening resilience and informing sustainable landslide disaster mitigation policies.